Identification, Characterization and Function of Orphan Genes Among the Current Cucurbitaceae Genomes - Ma, Dongna; Lai, Zhengfeng; Ding, Qiansu; Zhang, Kun; Chang, Kaizhen; Li, Shuhao; Zhao, Zhizhu; Zhong, Fenglin (Frontiers in Plant Science, 2022)
Orphan genes (OGs) that are missing identifiable homologues in other lineages may potentially make contributions to a variety of biological functions. The Cucurbitaceae family consists of a wide range of fruit crops of worldwide or local economic significance. To date, very few functional mechanisms of OGs in Cucurbitaceae are known. In this study, we systematically identified the OGs of eight Cucurbitaceae species using a comparative genomics approach. The content of OGs varied widely among the eight Cucurbitaceae species, ranging from 1.63% in chayote to 16.55% in wax gourd. Genetic structure analysis showed that OGs have significantly shorter protein lengths and fewer exons in Cucurbitaceae. The subcellular localizations of OGs were basically the same, with only subtle differences. Except for aggregation in some chromosomal regions, the distribution density of OGs was higher near the telomeres and relatively evenly distributed on the chromosomes. Gene expression analysis revealed that OGs had less abundantly and highly tissue-specific expression. Interestingly, the largest proportion of these OGs was significantly more tissue-specific expressed in the flower than in other tissues, and more detectable expression was found in the male flower. Functional prediction of OGs showed that 1) 18 OGs associated with male sterility in watermelon; 2) 182 OGs associated with flower development in cucumber; 3) 51 OGs associated with environmental adaptation in watermelon; 4) 520 OGs may help with the large fruit size in wax gourd. Our results provide the molecular basis and research direction for some important mechanisms in Cucurbitaceae species and domesticated crops.